Regulation and Effects of Gender Diversity on Corporate Boards: a Systematic Literature Review - Barnes-Culverwell, Ellinor (2022)
The underrepresentation of women on corporate boards is an ongoing issue, despite increasing pressures for firms to tackle it. Through the methodology of a restricted systematic literature review, this dissertation will analyse the scope of the academic literature published in the last six years, on the regulations and effects of corporate board gender diversity. From this, the dissertation finds that gaps previously identified in the research have not fully been addressed yet. This dissertation suggests that, as a result of this, future research should focus on the social impact of regulations and the effects increased corporate board gender diversity has on society. It also suggests that future research may produce more conclusive and consistent findings once more time has passed since regulations were introduced.